Recombinant Human Soluble Thrombomodulin Delivers Bounded Thrombin to Antithrombin III: Thrombomodulin Associates with Free Thrombin and Is Recycled to Activate Protein C - Aritomi, Masaharu; Watanabe, Naoko; Ohishi, Rika; Gomi, Komakazu; Kiyota, Takao; Yamamoto, Shuji; Ishida, Torao; Maruyama, Ikuro (Thrombosis and Haemostasis, 1993)
Recombinant human soluble thrombomodulin (rhs-TM), having no transmembrane domain or chondroitin sulfate, was expressed in Chinese hamster ovary cells. Interactions between rhs-TM, thrombin (Th), protein C (PC) and antithrombin III (ATIII) were studied. Equilibrium between rhs-TM and Th had no detectable time lag in clotting inhibition (Kd = 26 nM) or PC activation (Kd = 22 nM), while ATIII inhibited Th at a bimolecular rate constant = 5,200 M-1s-1 (Kd <0.2 nM). A mixture of ATIII, Th and rhs-TM showed that ATIII reacted with Th slower than rhs-TM, whose presence did not affect the reaction between ATIII and Th. In a mixture of rhs-TM, ATIII and PC, the repeated addition of Th caused the repeated activation of PC; which was consistent with the Simulation based on the assumption that rhs-TM is recycled as a Th cofactor. From these results, we concluded that upon inhibition of the rhs-TM-Th complex by ATIII, rhs-TM is released to recombine with free Th and begins to activate PC, while the Th-ATIII complex does not affect rhs-TM-Th equilibrium.